Directions for judgment and decision making research based on comparison selection: Reply to Arkes, Johnson, and Kardes. Issue 1 (12th October 2012) - Simonson, Itamar; Bettman, James R.; Kramer, Thomas; Payne, John W.
Abstract: Our target article proposed an alternative perspective for studying consumer judgment and decision making, focusing on the types and weights of comparisons consumers select. In this response we consider the major points made by each of the commentators and examine their implications for future work addressing our comparison‐focused approach.